2015
DOI: 10.1182/blood-2014-06-582924
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast ablation reduces normal long-term hematopoietic stem cell self-renewal but accelerates leukemia development

Abstract: • Bone marrow OB ablation leads to reduced quiescence, long-term engraftment, and self-renewal capacity of hematopoietic stem cells.• Significantly accelerated leukemia development and reduced survival are seen in transgenic BCR-ABL mice following OB ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(83 citation statements)
references
References 25 publications
2
79
0
Order By: Relevance
“…These studies argue that osteoblasts may be dispensable for HSC maintenance and self-renewal. Interestingly, Bhatia et al recently reported that osteoblast ablation did not result in a decrease in LTHSCs, but their long-term reconstitution and self-renewal capacities were impaired [33]. Tie-2-expressing HSCs could adhere to osteoblasts and stay in the quiescent state induced by angiopoietin-1 [34].…”
Section: Niche Cells Regulating Hscsmentioning
confidence: 99%
“…These studies argue that osteoblasts may be dispensable for HSC maintenance and self-renewal. Interestingly, Bhatia et al recently reported that osteoblast ablation did not result in a decrease in LTHSCs, but their long-term reconstitution and self-renewal capacities were impaired [33]. Tie-2-expressing HSCs could adhere to osteoblasts and stay in the quiescent state induced by angiopoietin-1 [34].…”
Section: Niche Cells Regulating Hscsmentioning
confidence: 99%
“…Some researchers tended to exclude the osteoblast niche from the HSC functional supporting cells because deleting either Scf or Cxcl12 using Col2.3-Cre did not affect HSC function in mice. However, recent evidence has shown that Col2.3-Cre induced osteoblast oblation in mice impaired HSC self-renewal function, though the overall number of HSCs did not significantly change [42,43]. This suggests that Col2.3-Cre marked osteoblasts might produce other unknown factors that contribute to maintaining HSC self-renewal potential.…”
Section: Identification Of Hsc Regulating Cells-a "Taking One Out" Stmentioning
confidence: 66%
“…Apparently, there took place a compensatory activation of the extramedullary hematopoiesis in the spleen and in the liver [80]. As a result of ablation of endosteal osteoblasts, the process of LT-HSCs self-renewal was disturbed while leukemia development was accelerated [81]. Thus essential role of the osteoblast that intercellular contacts in vitro produce a considerable influence on the functional, phenotypic and clonogenic properties of HSCs.…”
Section: Cd38mentioning
confidence: 97%